2017
DOI: 10.3390/min7030043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CaF2/CaO Composite Additive on Roasting of Vanadium-Bearing Stone Coal and Acid Leaching Kinetics

Abstract: Abstract:In this paper, the composite additive of CaF 2 /CaO was used to extract vanadium from stone coal, and the effect of roasting and leaching kinetics were studied. The purpose of this manuscript is to realize and improve the vanadium recovery from stone coal using the composite additive. The experimental results indicated that the roasted clinker can be obtained under the conditions of CaF 2 /CaO at a mass ratio of 2:3 and a total additive amount of 10 wt %, a roasting temperature 850 • C, and a roasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…It can be observed that the vanadium leaching efficiency continues to rise and reaches the maximum value at 1 h, and the vanadium leaching efficiency begins to decrease because of sintering [27] when the roasting time is above 1 h. Thus, the optimal roasting time is 1 h.…”
Section: Effect Of Different Additives and Their Dosage On The Vanadimentioning
confidence: 91%
See 1 more Smart Citation
“…It can be observed that the vanadium leaching efficiency continues to rise and reaches the maximum value at 1 h, and the vanadium leaching efficiency begins to decrease because of sintering [27] when the roasting time is above 1 h. Thus, the optimal roasting time is 1 h.…”
Section: Effect Of Different Additives and Their Dosage On The Vanadimentioning
confidence: 91%
“…Considering the fact that the particles are spherical, the irreversibility of the reaction, and the formation of the solid residual layer, it follows the typical nuclear contraction model, i.e., the shrinking core model (SCM) [27,30,31]. Drawn from this model, under vigorous stirring conditions, a control step of diffusion film can be ignored, focusing on the influence of the chemical reaction and diffusion rate on the leaching rate [27].…”
Section: Kinetics Analyses Of Vanadic Acid Leaching Processmentioning
confidence: 99%
“…Vanadium has been widely used in defense-related, aerospace, chemical industry, medicine, advanced materials, and other high-tech fields due to its unique physical and chemical properties [1][2][3][4][5][6]. In China vanadium-bearing shale is a dominant vanadium resource, and more than 87% of the vanadium exists in this unique vanadium resource [7][8][9]. Therefore, vanadium extraction from vanadium-bearing shale has been attracting enormous attention recently [10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is still a great possibility of improving the vanadium leaching efficiency. Generally, compared to a single additive, composite additives have been considered to work better in extracting vanadium due to the synergistic effect [14,21]. Furthermore, the deeper mechanism of vanadium extraction needs to be explained, such as the essence of vanadium extraction with roasting and the rule of vanadium migration and transformation.…”
Section: Introductionmentioning
confidence: 99%